Educational and Mothering Discourses and Learner Goals: Mexican Immigrant Women Enacting Agency in a Family Literacy Program - Blaire Willson Toso; Esther Prins (Adult Education Research Conference, 2010)
This paper, using data from a qualitative study, examines how Mexican immigrant women in a family literacy program appropriated mainstream discourses of mothering and parent involvement to pursue their personal and academic goals. The paper examines notions of human agency, prevailing parenting and literacy discourses, and learner goals and subjectivities.